Induction of VX2 para-renal carcinoma in rabbits: generation of animal model for loco-regional treatments of solid tumors. Issue 1 (December 2016) - Bimonte, Sabrina; Leongito, Maddalena; Piccirillo, Mauro; Tamma, Maria; Vallifuoco, Marianna; Bracco, Adele; Mancini, Antonio; Napoli, Daniele; Castaldo, Sigismondo; Cozzolino, Santolo; Iacobellis, Francesca; Grassi, Roberto; et al.
Abstract Background Animal models of para-renal cancer can provide useful information for the evaluation of tumor response to loco-regional therapy experiments in solid tumors. The aim of our study was to establish a rabbit para-renal cancer model using locally implanted VX2 tumors. Methods In order to generate a rabbit model of para-renal cancer, we established four hind limb donor rabbits by using frozen VX2 tumor samples. Following inoculation, rabbits were monitored for appetite and signs of pain. Viable tumors appeared as palpable nodules within 2 weeks of inoculation. Tumor growth was confirmed in all rabbits by high-resolution ultrasound analysis and histology. Once tumor growth was established, hind limb tumors extraction was used for tumor line propagation and para-renal tumor creation. Twenty-one rabbit models bearing para-renal cancer were established by implanting VX2 tumor into the para-renal capsula. Tumors developed into discreet 2–3 cm nodules within 1–3 weeks of implantation. Serial renal ultrasonography follow-up, starting 1 week after tumor implantation, was performed. Two weeks after tumor implantation, rabbits were euthanized and tumors and other organs were collected for histopathology. Results Tumor growth after VX2 tumor fragment implantation was confirmed in all rabbits by high-resolution ultrasound (US) imaging examinations of the para-renal regions and was measured with digital caliper. The para-renal injection of VX2 tumor fragments, achieved tumor growth in 100% of cases. All data were confirmed by histological analysis. Conclusions We generated for the first time, a model of para-renal cancer by surgical tumor implantation of VX2 frozen tumor fragments into rabbit's para-renal region. This method minimizes the development of metastases and the use of non-necrotic tumors and will optimize the evaluation of tumor response to loco-regional therapy experiments.